Synthesis and application of vinyl lactam block copolymer as kinetic hydrate inhibitors. (15th October 2019) - Long, Zhen; Ding, Qihang; Zhou, Xuebing; Liang, Deqing; Zhang, Guoying
Graphical abstract: Highlights: Block copolymer of N -vinyl caprolactam and acrylamide was synthesized. Higher-cloud-point PVCap- co -AM performed better than PVCap as KHIs on CH4 hydrate. PXRD and Raman results showed PVCap- co -AM did not alter hydrate crystal structure. Morphology of CH4 hydrate was clearly different between PVCap- co -AM and PVCap. Abstract: In this paper, a novel block copolymer poly ( N -vinyl caprolactam)- co -acrylamide) (PVCap- co -AM) was made from N -vinyl caprolactam (NVCap) with acrylamide (AM) by living radical copolymerization. The kinetic inhibitory performance of PVCap- co -AM on CH4 hydrate formation was firstly investigated and compared with PVP and PVCap. The results indicated that higher-cloud-point PVCap- co -AM behaved better than PVCap under the same conditions. Powder X-ray diffraction (PXRD) spectroscopy and Raman spectroscopy showed structure I hydrate was formed with and without KHIs. However, compared to pure water, the presence of KHIs reduced the ratio of large to small cage occupancy by CH4 . The stronger inhibition activity, the value became lower. Cryo-SEM images illustrated the morphology of CH4 hydrate crystals formed significantly varied by KHIs, which could be helpful for pipeline fluids safe transportation.